2006
DOI: 10.1097/01.ta.0000205861.29400.d9
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Patient Throughput on an Evolving Trauma/Emergency Surgery Service

Abstract: The initial improvements in patient throughput noted after the introduction of a CMT in January 1999 have been maintained in recent years despite the addition of an EGS component to the trauma service. Percent denied days and readmissions have continued to decrease. The length of stay for these patients remains, in part, dependent on other factors. The CMT plays an integral role in maintaining the efficiency of a trauma/emergency surgery service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Quality and efficiency research has shown that several interventions can improve the discharge process, with a proactive, defined approach. These include setting a target discharge date, formalizing a commitment to discharge goals with set discharge appointments, 12 leveraging night staff to jump start the discharge process, targeting long-stay patients with a consistent case manager, smoothing postYacute care transfers, eliminating documentation redundancies, and engaging clinical staff with the data for ongoing performance improvement pilots. 5,6,8 This leads to perhaps the most important lesson from this project: even when a process is in place, it needs continual maintenance, and new issues will continually arise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality and efficiency research has shown that several interventions can improve the discharge process, with a proactive, defined approach. These include setting a target discharge date, formalizing a commitment to discharge goals with set discharge appointments, 12 leveraging night staff to jump start the discharge process, targeting long-stay patients with a consistent case manager, smoothing postYacute care transfers, eliminating documentation redundancies, and engaging clinical staff with the data for ongoing performance improvement pilots. 5,6,8 This leads to perhaps the most important lesson from this project: even when a process is in place, it needs continual maintenance, and new issues will continually arise.…”
Section: Discussionmentioning
confidence: 99%
“…Case management was tasked to create a process whereby these patients are actively evaluated on a daily basis and brought to multidisciplinary rounds so that system problems or other barriers can be addressed. 12 It has been suggested that a reduction in the LOS actually has minimal effect on cost. 4 It is sure that the final day of hospital stay, particularly on trauma services, is often not an expensive day.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39] Hospital costs for orthopaedic trauma care are driven by implant costs and LOS, which become particularly important when reimbursement is fixed for a given diagnosis group or type of procedure. 40,41 One recent study on the management of patients with femoral shaft fractures showed that hospital costs could be contained with shorter lengths of stay.…”
Section: Discussionmentioning
confidence: 99%
“…20 Lastly, formalized multidisciplinary meetings that bring together the trauma service, major surgical consultants, and other ancillary support services have been shown to improve patient throughput. 21,22 A decreased patient hospital length of stay for any given disease process is a marker of overall efficiency. We described a novel method of efficiency improvement that required little to no change in staffing pattern nor does it require any noticeable upfront cost; it is merely a modification of an existing process.…”
Section: Discussionmentioning
confidence: 99%